Development of psychological and pedagogical classes of the Orenburg region - Artur M. Allagulov; Ol'ga V. Kuz'menkova; Natal'ja V. Drozdova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper contains the results of the study on the development of psychological and pedagogical classes in the Orenburg region. The relevance of the study is due to the growing importance of the profile training of senior students of general educational institutions, focused on the teaching profession. Based on the analysis of scientific sources and the accumulated pedagogical experience, the dynamics of the development of psychological and pedagogical classes from the moment of inception to the present day is traced. As the study showed, this phenomenon has not been fully studied in pedagogical science and practice. The aim of the study is to reconstruct the development of psychological and pedagogical classes in Russia and the Orenburg region. The basic methods were: the method of reconstruction, historical and genetic analysis, the method of analytical generalization. The source base of the study was made up of official normative legal documents regulating the development of psychological and pedagogical classes in the 19th21st centuries, as well as a set of publications on the problem under study. Based on the results of the study, it was concluded that the phenomenon under study has passed a long stage in its development. There are two key stages in its development the second half of the 19th century until the 1960s, when the pedagogical class was considered as one of the forms of training teachers, and from the 60s of the 20th century to the present day this is a form of pre-profile and profile training of students for the teaching profession. Based on the results of the study, recommendations are given on the need to introduce a systematic and productive practice of networking between general educational organizations, on the one hand, and pedagogical universities, on the other, with the organizational support of education authorities. The introduction of this model will make it possible to move forward in solving an urgent problem for the education system of the Russian Federation the lack of teaching staff.